FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ANGKA KEJADIAN MIOPIA DI SMPN 2 MOJOKERTO - Kusumawardhany, Rini; Dharianta, Rifqy (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Factors related to myopia are close-range activities, such as reading, writing, using computers and gadgets. Myopia is also related to the environment, namely spending time outdoors and genetic factors. Objective: The aim of this research was to show whether there is an influence between behavioral and genetic factors on the incidence of myopia in students at SMPN 2 Mojokerto City. Method: The research method used in this research is the Cross-Sectional Study analytical method, namely research to identify through observation using a questionnaire conducted online. The sampling technique used was simple random sampling. The number of samples in this study was 165 children. Data were analyzed univariately and bivariately using the Chi-Square statistical test via SPSS version 24. Results: The results of the study showed that all variables, namely length of use of devices (screen time) with p-value = 0.000, genetic factors of parents with p-value = 0.000, length of outdoor activities with p-value = 0.006, and length of sleep time with p-value = 0.000, showed a significant relationship to the incidence of myopia while position using a device with p-value = 0.239 does not show a significant relationship. Conclusion: It is hoped that the results of this research can provide education to children so that myopia does not increase by regulating the duration of use of devices/laptops (screen time) in a day for close activities, increasing the time for outdoor activities and the amount of sleep a day.